Power, Discourses and Accounting Change: The Implementation of Activity Based Costing in a Portuguese Bank - Vieira, Rui; Hoskin, Keith (Anais do Congresso Brasileiro de Custos - ABC)
This paper, based in a longitudinal case study of organisational change, explores the implementation process of an activity based costing (ABC) system in a Portuguese bank. It discusses several issues raised during the implementation, linking theory and practice, in line with Morgan and Sturdy (2000) framework that enables the exploration of the effect of accounting practices on change across time from three perspectives - changing structures, changing discourses and the effect of both of these processes on power relations. Located in a wider cultural change in Portuguese banking towards global (i.e. US derived) strategies and processes, but within an organizational world where older traditions remain powerful, the ABC project was not initially recognised as a strategic initiative. The lack of a clear supportive attitude, namely through the involvement of someone from top management, made the ?turf wars? between the departments involved the central issue, while other factors identified by the literature as key to a successful implementation become secondary. The research highlights that accounting becomes more visible in the organisation and so perceived, at the level of what people say and write, as important to it. ABC was perceived as a system that could provide relevant information and it has overcome the barrier of accounting being the exclusive domain of the accounting department.